2021
DOI: 10.3390/cancers13236107
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Prime-Boost Vaccination with a Peptide-Based Vaccine and Viral Vector Reshapes Dendritic Cell, CD4+ and CD8+ T Cell Phenotypes to Improve the Antitumor Therapeutic Effect

Abstract: Heterologous prime-boost settings with a protein vaccine and the viral vector vesicular stomatitis virus, both expressing tumor-associated antigens (KISIMA-TAA and VSV-GP-TAA), have been previously shown to generate potent antitumor immunity. In the cold TC-1 model (HPV antigen) and the immune-infiltrate MC-38 model (Adpgk, Reps1 and Rpl18 neo-antigens), we further investigated pivotal immune cells that educate CD8+ T cells. Heterologous prime-boost vaccination induced a superior antitumor response characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The combination of protein-based cancer vaccine with oncolytic virus in heterologous prime-boost setting has been previously shown to elicit a robust and durable antigen-specific CD8 T cell response associated with a profound remodeling of the tumor microenvironment, resulting in strong tumor growth inhibition in mouse models [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of protein-based cancer vaccine with oncolytic virus in heterologous prime-boost setting has been previously shown to elicit a robust and durable antigen-specific CD8 T cell response associated with a profound remodeling of the tumor microenvironment, resulting in strong tumor growth inhibition in mouse models [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…KISIMA—VSV-GP-TAg heterologous prime-boost is a vaccination strategy combining the protein-based cancer vaccine with the oncolytic virus expressing the same tumor antigens. We have previously shown that therapeutic vaccination with KISIMA—VSV-GP-TAg resulted in significantly improved antitumoral efficacy in different mouse tumor models [ 7 , 8 ]. Mechanistically, KISIMA—VSV-GP-TAg vaccination not only elicited a strong peripheral antigen-specific CD8 T cell response but also induced a deep remodeling of the tumor microenvironment (TME) by promoting a significant influx of cytotoxic CD8 T cells and cross-presenting dendritic cells and by decreasing the presence of immune suppressive cells such as M2 tumor associated macrophages (TAM-2) and myeloid derived suppressor cells (MDSCs) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides an opportunity for vaccine-induced neoantigen-specific CD4 + T cells to provide optimal help and stimulate tumor-specific CD8 + T cells, which can then re-enter the circulation and home to the tumors to kill malignant cells. 53 In addition to their role in the tumor-draining lymph nodes, tumor-specific CD4 + T cells residing in the TME can contribute to tumor resistance, for example, by recruiting 54 , 55 , 56 and providing local help to 57 CD8 + T cells. Which of these mechanisms contributed to the efficacy of the neoHELP vaccine is at present unclear and will be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…These engineered viruses have some potential in the delivery of antitumor drugs [233]. Pioneering therapeutic strategies, such as the KISIMA/VSV-GP heterologous prime-boost methodology and the development of adenovirus-based tumor vaccines, have further emphasized the potential of oncolytic virotherapy as a formidable armament in the arsenal of cancer immunotherapy [234].…”
Section: Cancer Vaccine + Oncolytic Virotherapymentioning
confidence: 99%